Professional Growth And Staff Development (How To Encourage Employees To Pursue Professional Development - Bambang Purwanto, Muhammad (International Journal of Technology and Education Research, 2023)
Professional growth is seen as an overall developmental process that takes place during one’s career and lifespan and understood as an umbrella term, and an overlapping term, to other related concepts. Furthermore, we argue that professional growth is dependent on the social and institutional contexts as well as personal attributes and circumstances. Following this, a model containing three dimensions related to learning in professional contexts (formal–informal, situated–unsituated and individual–social learning) is presented. The model is formed to illustrate that promotion of professional growth in workplaces is connected to formal and informal practices, versatility of working environments, as well as social relations. The chapter concludes with discussion and future research suggestions related to conceptual issues with regards of professional growth and contemporary challenges of in working life.